The effect of antenatal corticosteroids on maternal glycemic control, in a tertiary care centre in North Kerala - India - B., Beena; K., Libu G.; S., Akhila M.; Chandran, Jyothi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Antenatal glucocorticoid therapy (ACT) can be life-saving in preterm babies and risk of PTL is increasing in. The prevalence of GDM also increasing. Virtually, all women will experience deterioration in their glycaemic control following ACT. The NICE guideline recommends additional insulin and the national Indian guidelines recommend a 20% increase. Objective of this study was to evaluate the changes in maternal serum glucose following corticosteroids in antenatal women. Methods: Prospective controlled trial of 206 patients, divided into 2 groups. Group 1:105 patients with no GDM and Group 2: 101 patients with GDM. Ethical committee approved. FBS and PPBS measured for following 5 days of D1. BMI and starting dose of insulin and dose of insulin hike were recorded. FBS >90 mg/dL and PPBS >120 mg/dL were taken as abnormal. Data were analyzed using SPSSV22. Results: There were a total of 206 of which 105 were in group 1(51%) and 101(49%) were in Group 2. FBS >90 mg/dL in over 65% of all women on D2 10 new cases on D3 and PPBS >120 mg/dL in over 66% of all women on D2 and 13 new cases on D3. Insulin was started in a total of 66 patients of 105 (62.9%) in Group 1 and 33 out of 40 (82.5%) in GDM on MNT. Of the 66 patients who started on insulin in Group 1, 17 (16.2%) patients had to continue insulin and out of 33. In MNT subgroup 10 (25%) had to continue. BMI was high in the patients, who was given and continued insulin. Conclusions: The findings support the concept of increasing the dose of insulin even before the hyperglycemia documented. In the Group 1 66 of 105 patients were started on insulin due to hyperglycemia and 17 had to continue insulin 25.7%), and 33 of 40 patients in GDM on MNT were started on insulin and 10 (30.33%) had to continue. We suggest testing all patients for hyperglycemia and to start insulin especially in the those with high BMI (>25 as per the Asian Indian).